Clinical efficacy and safety of trimonthly administration of goserelin acetate 10.8 mg in premenopausal Chinese females with symptomatic adenomyosis: a prospective cohort study. (14th December 2023) - Sun, Hao; Yuan, Ming; Wang, Xinyu; Jiao, Xue; Pan, Zangyu; Li, Hua; Yang, Linqing; Wang, Liming; Zhang, Shihong; Ren, Qianhui; Yan, Shumin; Li, Dong; et al.
Abstract: Objective: This prospective cohort study aimed to compare the clinical efficacy and safety of goserelin 10.8 mg administered trimonthly with goserelin 3.6 mg administered monthly in premenopausal females with symptomatic adenomyosis. Methods: We recruited 139 premenopausal females with adenomyosis who complained of dysmenorrhea and/or menorrhagia. The first group ( n  = 70) received a single subcutaneous injection of goserelin 10.8 mg, and the second group ( n  = 69) received monthly subcutaneous goserelin 3.6 mg administered for 3 months. Follow-up was performed at the outpatient department after 12 weeks. Results: Ultimately, 130 patients completed the study, including 68 and 62 patients in the goserelin 10.8 mg ( n  = 70) and 3.6 mg ( n  = 69) groups, respectively. We observed a significant decrease in the dysmenorrhea (NRS) score, uterine volume, and cancer antigen 125 (CA125) levels, and a significant increase in hemoglobin (HGB) levels in both treatment groups. There was no significant difference between the two groups. The sum of the adverse event scores was slightly higher in the goserelin 3.6 mg than in the 10.8 mg group. Conclusions: The clinical efficacy of trimonthly administration of goserelin 10.8 mg was equivalent to monthly 3.6 mg dosing and was non-inferior regarding safety and tolerability. Hence, it can be a more cost-effective and convenient alternative treatment option in premenopausal females with symptomatic adenomyosis. Trial registration: ChiCTR2200059548